Chrześcijanie i poganie. O problemach interpretacji odkryć archeologicznych związanych z początkami chrześcijaństwa na ziemiach polskich. - Buko, Andrzej (Slavia Antiqua. Rocznik poświęcony starożytnościom słowiańskim, 2016)
Mediaeval historians as well as archaeologists have been intrigued by the beginning of Christianity in Poland. The interest intensified in 2016 when the country celebrated the 1050th anniversary of the baptism of Poland. The accompanying discussions indicate that facing the ambiguous written sources, researchers still disagree about fundamental data like the year and the location of the baptism, its circumstances or material evidence of the events. An argument was put forward that in this context, celebrating the 1050th anniversary of the baptism of Poland is groundless. Attention was drawn to the fact that baptism of the ruler and his entourage did not affect the country’s inhabitants who remained pagans for a long time afterwards. In this article, I highlight some aspects of the research and the controversy surrounding the interpretation of archaeological finds from the beginning of Christianity in Poland. I also indicate other possibilities of interpreting the existing archaeological sources and the possible ways in further research.